2019
DOI: 10.1111/tri.13491
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early bleeding complications after lung transplantation – a retrospective cohort study

Abstract: Risk factors for early bleeding complications after lung transplantation are not well described. Our aim was to evaluate coagulation test results and the use of extracorporeal membrane oxygenation as risk factors for bleeding after lung transplantation. We analyzed a single-center cohort of bilateral lung transplants between January 2009 and August 2015. Predictors of severe postoperative bleeding (bleeding requiring reoperation within 48 h of transplantation) were assessed using multivariable logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Because of longterm intravascular catheterization and the use of anticoagulants, the risk of thrombosis and bleeding after LT increases greatly in ECMO bridging patients. An astonishing 25.41% (47/185) incidence of postoperative bleeding (requiring reoperation) was found in the BTT group, accompanied by more blood transfusions (mean RBC transfusion: 20.4 u vs. 8.9 u, RR = 12.11) compared with the non-BTT group.Adelmann et al analyzed the risk factors of bleeding complicationsafter LT and reported similar results 34. After ECMO implantation, acquired von Willebrand syndrome (ACWS) can occur in 24 hours and is hard to diagnose with routine coagulation tests 35.…”
mentioning
confidence: 90%
“…Because of longterm intravascular catheterization and the use of anticoagulants, the risk of thrombosis and bleeding after LT increases greatly in ECMO bridging patients. An astonishing 25.41% (47/185) incidence of postoperative bleeding (requiring reoperation) was found in the BTT group, accompanied by more blood transfusions (mean RBC transfusion: 20.4 u vs. 8.9 u, RR = 12.11) compared with the non-BTT group.Adelmann et al analyzed the risk factors of bleeding complicationsafter LT and reported similar results 34. After ECMO implantation, acquired von Willebrand syndrome (ACWS) can occur in 24 hours and is hard to diagnose with routine coagulation tests 35.…”
mentioning
confidence: 90%
“…Overall, the duration of mechanical ventilation in our cohort was in line with published data where a 65% of respondents aiming for extubation at 36 hours postoperative 7 , bearing in mind that avoidance of long periods of mechanical ventilation may protect against deleterious effects of recently implanted graft 8 . In a recently published study severe postoperative hemorrhage was associated with use of pre or post-operative ECMO and it was linked to worse 60-day survival after lung transplantation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…This cohort was also used in a previous study assessing bleeding complications after lung transplantation. 15 The primary outcome of this study was postoperative mortality during the first year following transplantation. Secondary outcomes were acute kidney injury using 'Kidney Disease Improving Global Outcomes' (KDIGO) criteria during the first week after surgery 17 , time to postoperative extubation, and primary graft failure assessed by a transplant pulmonologist following current guidelines.…”
Section: Methodsmentioning
confidence: 99%